Potential of bipolaris bicolor in combination with ametryn for inhibition of Glyphosate-resistant goosegrass Eleusine indica biotypes - Fakri, Muhammad Aiman; Ghazali, Nur Faqihah; Sapak, Zaiton; Ahmad Hamdani, Muhammad Saiful; Chuah, Tse Seng (Friends Science Publishers, 2022)
Fungal pathogens have been investigated previously for biological control of goosegrass (Eleusine indica), but there is little research on the compatibility of herbicides with fungal pathogen Bipolaris bicolor for control of glyphosate-resistant E. indica. The aims of this study were to 1) examine the in vitro compatibility of Bipolaris bicolor and three herbicides (ametryn, flumiozaxin and sodium chlorate) and 2) determine the efficacy of a combination of B. bicolor and ametryn for inhibiting glyphosate-resistant E. indica biotypes in the greenhouse. Mycelial growth inhibition area was measured after B. bicolor spores were treated with ametryn, flumiozaxin, or sodium chlorate at one-fifth of their recommended rates. The findings showed that ametryn had the lowest inhibitory effect (10%), while flumioxazin and sodium chlorate had 80 and 30% inhibition, respectively, indicating that ametryn is the most compatible herbicide with B. bicolor. E. indica seedlings were then subjected to four treatments, including non-treated plants, at the 3 to 4-leaf stage where T1: negative control plant, T2: onefifteenth of the recommended dose of ametryn, T3: B. bicolor spore suspension and T4: ametryn plus B. bicolor sporesuspension. B. bicolor in combination with ametryn was the most effective treatment for E. indica inhibition one week after treatment. The treatment reduced seedling height, leaf greenness and shoot dry weight by 50 to 94% and caused plant death seven days after treatment. These findings suggest that B. bicolor in combination with ametryn is a viable integrated strategy to control the glyphosate-resistant E. indica biotype